The Role of the Temple Mount / Al-Haram Al-Sharif in the Deterioration of Muslim–Jewish Relations - Moshe Ma'oz (Approaching Religion, 2014)
For both Jews and Muslims the Temple Mount and the Old City of Jerusalem constitute highly important religious, cultural, political and national centres. For centuries Jews in the diaspora prayed in the direction of Jerusalem, vowed never to forget it (‘If I forget thee Jerusalem, may my right arm wither’); and blessed one another ‘Next year in Jerusalem’. The Zionist-Jewish movement (since the 1880s) – although predominantly secular – has considered Jerusalem (Zion) as the political and cultural centre of the Jewish people.By comparison, the Palestinian-Arab national movement has, since the 1920s established its national and political-cultural centre in East Jerusalem, while the Haram al Sharif, particularly the Al-Aqsa Mosque, has continued to be a top religious shrine for Muslims. They termed it Awla Al-Qiblatayn (the first prayer direction before Mecca); Thani Masjidayn (the second mosque after Mecca); a place where Prophet Muhammad ascended to heaven (Isra’ and Mi’raj).This article will examine the changes in Muslim–Jewish mutual relations, especially since 1967, at both government and public levels. Special attention will be given to the development of both Islamic Judeophobia and Jewish Islamophobia, which have been associated with the dispute over the Temple Mount and East Jerusalem.